Design of Data Crawling System Based on Python - Taking House Information Crawling as an Example - Mao, Hongxia (Journal of Theory and Practice of Engineering Science, 2024)
The extensive application of Internet technology has led to the explosive growth of network resources. Finding the required data in the massive data is a time-consuming and labor-intensive thing. Housing information is one of the hot topics of national concern, and the use of web crawling technology can quickly and accurately obtain housing information from various platforms. This article uses Python language combined with web crawling technology to design a house information data crawling system, which includes modules such as URL manager, webpage download, webpage analysis, data collection, and data storage. Successfully saved the house information and pictures on the target website through the operation of the system.